2020
DOI: 10.1186/s12888-019-2425-8
|View full text |Cite
|
Sign up to set email alerts
|

Stratified analyses of genome wide association study data reveal haplotypes for a candidate gene on chromosome 2 (KIAA1211L) is associated with opioid use in patients of Arabian descent

Abstract: Background: Genome Wide Association Studies (GWAS) have been conducted to identify genes and pathways involved in development of opioid use disorder. This study extends the first GWAS of substance use disorder (SUD) patients from the United Arab Emirates (UAE) by stratifying the study group based on opioid use, which is the most common substance of use in this cohort. Methods: The GWAS cohort consisted of 512 (262 case, 250 controls) male participants from the UAE. The samples were genotyped using the Illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Inspecting the genes in our meta-analysis, using VEP revealed that NIPA1, KIAA1211L, AFF3, and TSGA10 are genes affected by variants in this region. Copy number variations in NIPA1 were found in psychiatric disorders [39], KIAA1211L was identified in a schizophrenia twin-study [40] and is a candidate gene for opioid abuse [41], and AFF3 is involved in intellectual disability and cellular migration in the cerebral cortex of mice [42]. The studies mentioned make those genes likely candidates to influence the trait pEFP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspecting the genes in our meta-analysis, using VEP revealed that NIPA1, KIAA1211L, AFF3, and TSGA10 are genes affected by variants in this region. Copy number variations in NIPA1 were found in psychiatric disorders [39], KIAA1211L was identified in a schizophrenia twin-study [40] and is a candidate gene for opioid abuse [41], and AFF3 is involved in intellectual disability and cellular migration in the cerebral cortex of mice [42]. The studies mentioned make those genes likely candidates to influence the trait pEFP.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the trait pEFP we could confirm a QTL on GGA1 that was previously identified [6], which in our study contains variants affecting NIPA1, KIAA1211L, AFF3, and TSGA10. All of those genes, except TSGA10, have been implicated in neurological conditions [39][40][41][42] making them additional targets for genomic selection against FP.…”
Section: Discussionmentioning
confidence: 99%
“…CRACD downregulation has been strongly associated with various types of cancer and metastasis, including small cell lung carcinoma 41 , and colorectal cancer stem cells 42 . Haplotypes of CRACD have been linked to opioid use in patients, as indicated by a recent genome-wide association study (GWAS) 43 . During development, CRACD is expressed during early timepoints and is thought to play a role in tissue differentiation, particularly in the heart and both peripheral and central nervous systems.…”
Section: Discussionmentioning
confidence: 99%
“…CRACD downregulation has been strongly associated with various types of cancer and metastasis, including small-cell lung carcinoma [60] and colorectal cancer stem cells [61]. Haplotypes of CRACD have been linked to opioid use in patients, as indicated by a recent genome-wide association study (GWAS) [62]. During development, CRACD is expressed during early timepoints and is thought to play a role in tissue differentiation, particularly in the heart and both the peripheral and central nervous systems.…”
Section: Discussionmentioning
confidence: 99%